Perception and Mental Health Status Regarding COVID-19 Vaccination Among Taiwanese Adolescents and Their Caregivers - Hwang JW; Chien SJ; Wang CC; Kuo KC; Tang KS; Lee Y; Chen YC; Lo MH; Lee IK; Chuah SK; Lee CT; Kung CT; et al. (Dove Medical Press, 2023)
Jade Winjei Hwang,1 Shao Ju Chien,2 Chih-Chi Wang,3 Kuang-Che Kuo,4 Kuo-Shu Tang,5 Yu Lee,1 Yi-Chun Chen,6 Mao-Hung Lo,2 Ing-Kit Lee,6 Seng-Kee Chuah,7 Chien-Te Lee,8 Chia-Te Kung,9 Liang-Jen Wang10 1Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 2Division of Pediatric Cardiology, Kaohsiung Chang Gung Memorial Hospital and College of Medicine, Chang Gung University, Kaohsiung, 83301, Taiwan; 3Division of General Surgery, Department of Surgery, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 4Division of Pediatric Infection, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, 83301, Taiwan; 5Division of Pediatric Emergency, Kaohsiung Chang Gung Memorial Hospital, Kaohsiung, 83301, Taiwan; 6Division of Infectious Disease, Department of Internal Medicine, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 7Division of Hepato-Gastroenterology, Department of Internal Medicine, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 8Department of Nephrology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 9Department of Emergency, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 10Department of Child and Adolescent Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, TaiwanCorrespondence: Liang-Jen Wang, Department of Child and Adolescent Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, No. 123, Ta-Pei Road, Kaohsiung, Taiwan, Tel +886-7-7317123 Ext 8753, Fax +886-7-7326817, Email wangliangjen@gmail.comBackground: Vaccinating adolescents is a vital strategy to enhance population protection without imposing overly restrictive measures on our daily lives during the COVID-19 pandemic. As teenagers gain more independence, their willingness to get vaccinated may depend on their own understanding of the pandemic, vaccines, and mental well-being, as well as that of their caregivers. Our study aimed to examine how Taiwanese adolescents and their caregivers perceive COVID-19 vaccination and assess their mental health status.Methods: We invited a total of 138 vaccinated adolescents and their caregivers to complete several questionnaires, including the Drivers of COVID-19 Vaccination Acceptance Scale (DrVac-COVID19S), Impact of Event Scale (IES), and Chinese Health Questionnaire (CHQ).Results: Among the adolescents, 76.8% considered the BNT162b2 vaccine (Pfizer-BioNTech) as the ideal option for COVID-19 vaccination, while 27.5% of caregivers expressed acceptance of any available vaccine. Adolescents scored higher than caregivers in terms of vaccine value (p< 0.001) and autonomy (p< 0.001), but lower in knowledge (p< 0.001), as assessed by the DrVac-COVID19S subscales. The adolescents' intention to get vaccinated against COVID-19 (DrVac-COVID19S total score) showed a positive correlation with their perception of the pandemic's impact (IES scores, r=0.214, p=0.012) and their caregivers' vaccination intention (r=0.371, p< 0.001). Furthermore, adolescents' mental health demonstrated a positive association with the mental health of their caregiver (CHQ total scores, r=0.481, p< 0.001).Conclusion: During the COVID-19 outbreak, caregivers have encountered heightened levels of mental stress, and this stress has been found to be positively correlated with the mental stress experienced by adolescents and their intentions regarding vaccination. These findings can serve as crucial references for healthcare providers and governments when formulating vaccination policies for adolescents in the future.Keywords: adolescent, autonomy, caregivers, vaccine, psychosomatic, SARS-Cov-2